ROBUST REGRESSION FOR ESTIMATING THE IMPACT OF STUDENT’S SOCIAL BEHAVIORS ON SCIENTIFIC LITERACY - Umi Mahmudah; Muhamad Chamdani; Tarmidzi Tarmidzi; Siti Fatimah (Jurnal Cakrawala Pendidikan, 2020)
Scientific literacy is a vital program for current generation of students in the whole world. The purpose of this study is to estimate the impact of students’ social behaviors on scientific literacy by using robust regression. A robust approach is applied to overcome the weaknesses of the ordinary least squares (OLS) regression model. The method is believed to produce better accuracy of estimation. This study applies a survey method conducted by using 200 research subjects which are randomly selected at a university in Indonesia. There are two instruments used, namely questionnaire sheets using a Likert scale and test sheets. There are four categories used in this study to measure the students’ social behaviors, which are cooperation (X1), assertiveness (X2), self-control (X3) and pro-social behaviors toward peers (X4). The analysis results reveal that all of independent variables have positive and significant impact on students’ scientific literacy (Y). Furthermore, the highest impact is collaboration (X1) and the lowest impact is pro-social behavior towards peers (X4), where the robust regression coefficients are .262 and .238, respectively.